Gibberellic acid (GA) role in acetyl-coA carboxylase enzyme regulation and in improving oil palm yield - Irma Kresnawaty; Djoko Santoso; Galuh Wening Permatasari; Sumi Hudiyono (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2023)
Seaweed specifically, Sargassum sp. is known to contains a boosting hormone growth that has been promoted plant growth and yield due to the containing of auxin, gibberelic acid (GA) and cytokinine, and also some amino acids especially glutamic acid. Those composition could be used as an booster of palm oil production which related to acetyl co-A carboxylase activity (ACC). ACC is the rate determination step in fatty acid accumulation, and becomes active through dephosphorylation of some serine residues that induced by magnesium and glutamate. Moreover, ACC was regulated by AtWRI1 and AtWRI1-TCP4 interaction, a mechanism that allow fine-tuning of the oil biosynthetic pathway. In this research we conducted gene expression experiments, and molecular docking analyses to study the possible mechanism of seaweed composition stimulating oil accumulation in the oil palm. Further analysis was conducted to ensure whether the interaction between TCP4 and candidate inhibitors were able to phosphorylate TCP4 and decrease its activity. GA application resulted in the increase of oil accumulation in 1 month after application, although in the second month the oil accumulation showed decreasing. Increase of oil accumulation in the first month in line with the increase of the expression of ACC in 3rd and 5th weeks. Meanwhile, TCP4 showed decrease expression that resulted in the increase of the WRI1 in 5th week. From this result, it was indicated that GA application could block the TCP4, so it could not interact with WRI1, resulted in the expression of WRI1 and ACC. This interaction stimulates the oil accumulation in oil palm.